Design of Data Management Information System for Real Work Practices at the Faculty of Teacher Training and Education, Sebelas Maret University, Surakarta: Perancangan Sistem Informasi Pengelolaan Data Praktek Kerja Nyata di Fakultas Keguruan dan Ilmu Pendidikan, Universitas Sebelas Maret Surakarta - Sumarno, Sumarno; Pantjarani, Ari; Naury, Chairullah (Politeknik Harapan Bangsa Surakarta, 2023)
Real Work Practice (PKN) is one of the academic activities that must be followed by all students in study programs at the Teaching and Education Faculty (FKIP) Sebelas Maret University Surakarta (UNS). The implementation of Internship is an obstacle for FKIP UNS which has students from various regions and these students choose their own place for the Internship. FKIP UNS will find it difficult to monitor students in carrying out PKN if the accompanying lecturers have to visit one by one where students carry out PKN. This makes the goal of FKIP UNS in providing work experience in the real world not well achieved. From the problems above, the researcher proposes to design a web-based PKN data management information system at FKIP UNS. The formulation of the problem that the researcher will solve in this study is,